Perancangan Sistem Informasi Pencatatan, Penghitungan, Rekap Hasil Panen Berbasis Mobile Programming (Current Research in Education: Conference Series Journal, 2023)
The function of information technology systems is very useful in various business sectors, one of which is in the field of agriculture. Agriculture in the Indramayu Regency area is one of several areas that have natural wealth and natural resources originating from agriculture in the rice and rice sector. Utilization of information systems can run optimally considering the rotation of harvest and sales in the rice and rice sector is so fast. To facilitate the data collection, an information system is needed that can facilitate the collection of data on how much harvest is done by each worker who assists in carrying out the harvest. This study aims to design an information system that can record, calculate, and recap crop yields and be an answer for farmers who still record in the traditional way. The research method used by the researcher is Research and Development. From the research conducted, a warehouse management information system software based on Mobile Programming was produced with the feature of recording the work of each worker who worked on the harvest day and also the total amount of harvest on that day, and recap all records of rice and rice entering and leaving storage.